Dampak Sosial dan Ekonomi Pasar Murah di Lingkungan Lokal Kantor Camat Medan Baru - Hasibuan, Zuhri Fitransyah; Pirandy, Gusti; Ritonga, Fajar Utama (Medan Resource Center, 2023)
This study investigated the social and economic impacts of the cheap market in the local environment, focusing on the sub-district office of Medan Baru. Data collection methods include interviews, surveys, and documentary analysis. Results show that the cheap market contributes significantly to the welfare of the local community by improving accessibility to basic consumer goods and providing business opportunities for local traders. Socially, the cheap market strengthens social cohesion and facilitates cultural exchange among the local population. Economically, the presence of cheap markets boosts local economic growth by increasing traders' income and reducing the cost of living for the community. The findings provide valuable insights for local governments and relevant stakeholders to improve and support the cheap market program in promoting social inclusion and economic growth in local communities.